Pauses and turn-taking in a multi-level language ability adult Efl group: A case study - Selinay Gündoğan (Yayasan Mitra Persada Nusantara, 2026)
As globalization diversifies adult education, English as Foreign Language (EFL) classrooms increasingly function as heterogeneous communities comprising mixed ages and proficiency levels. Despite this shift, existing literature largely treats these variables in isolation, overlooking the complex interplay between linguistic ability and generational dynamics. This case study addresses this gap by analyzing a multi-level, multi-age adult EFL group through Conversation Analysis (CA), grounded in the theoretical framework of Activity Systems. The study examines how classroom interaction is co-constructed not only through linguistic competence but also through social norms and age-related hierarchies. Data analysis reveals distinct micro-interactional patterns: brief pauses function as structural tools for task management, while frequent latching emerges as a primary mechanism for peer scaffolding within adjacency pairs. Most significantly, the study uncovers how social rules within the activity system mediate linguistic performance. Findings indicate a critical intersection of age and proficiency, where longer pauses frequently signal younger participants deferring to older peers. This suggests that turn-taking is governed by a social etiquette of respect that surpasses linguistic processing speed. The study concludes that the adult EFL classroom is a multi-dimensional activity system where social identity and language proficiency are inextricably linked, calling for a pedagogical shift that acknowledges these complex, underlying dynamics in mixed-ability groups.